Antisense oligonucleotide targeting nicotinamide N-methyltransferase exhibits antitumor effects - Tomoaki Hara; Sikun Meng; Yuuya Kasahara; Takashi Osawa; Daisuke Motooka; Hiromichi Sato; Yasuko Arao; Yoshiko Saito; Kana Inoue; Yumiko Hamano; Yuichiro Doki; Hidetoshi Eguchi; et al. (Molecular Therapy: Nucleic Acids)
Nicotinamide N-methyltransferase (NNMT) is one of the methyltransferase family genes. It consumes S-adenosyl-l-methionine (SAM), which is required for DNA methylation and histone methylation for epigenetic regulation, to produce 1-methylnicotinamide from nicotinamide, a source of NAD+, thus affecting energy metabolism and epigenetics. Recent studies have shown that NNMT is highly expressed in cancer tissues, mainly in the stroma, and worsens prognosis. Therefore, NNMT is attracting attention as a new target for cancer therapy. In this study, we generated 2′,4′-BNA/LNA-modified gapmer phosphorothioate antisense oligonucleotides that inhibit NNMT expression and examined their antitumor effects. The antisense oligonucleotide candidates were finally narrowed down to eight sequences, and when they were examined for their inhibitory effect on NNMT expression in cancer cells, all of the sequences showed inhibitory effects. The most effective one was conjugated with a small molecule compound that targets the stroma of cancer tissues. The antitumor effect was examined in a mouse model of cancer cell transplantation, and the antitumor effect was enhanced in the group treated with the antisense oligonucleotide. These results indicate that NNMT antisense oligonucleotide drugs targeting the stroma are promising as novel anticancer agents.